Combined antitumoral effects of pretubulysin and methotrexate. Issue 1 (22nd January 2019) - Kern, Sarah; Truebenbach, Ines; Höhn, Miriam; Gorges, Jan; Kazmaier, Uli; Zahler, Stefan; Vollmar, Angelika M.; Wagner, Ernst
Abstract: Pretubulysin (PT), a potent tubulin‐binding antitumoral drug, and the well‐established antimetabolite methotrexate (MTX) were tested separately or in combination (PT+MTX) for antitumoral activity in L1210 leukemia cells or KB cervix carcinoma cells in vitro and in vivo in NMRI‐nu/nu tumor mouse models. In cultured L1210 cells, treatment with PT or MTX displays strong antitumoral effects in vitro, and the combination PT+MTX exceeds the effect of single drugs. PT also potently kills the MTX resistant KB cell line, without significant MTX combination effect. Cell cycle analysis reveals the expected arrest in G1/S by MTX and in G2/M by PT. In both cell lines, the PT+MTX combination induces a G2/M arrest which is stronger than the PT‐triggered G2/M arrest. PT+MTX does not change rates of apoptotic L1210 or KB cells as compared to single drug applications. Confocal laser scanning microscopy images show the microtubule disruption and nuclear fragmentation induced by PT treatment of L1210 and KB cells. MTX changes the architecture of the F‐actin skeleton. PT+MTX combines the toxic effects of both drugs. In the in vivo setting, the antitumoral activity of drugs differs from their in vitro cytotoxicity, but their combination effects are more pronounced. MTX on its own does not display significant antitumoral activity, whereas PT reduces tumor growth in both L1210 and KB in vivo models. Consistent with the cell cycle effects, MTX combined at moderate dose boosts the antitumoral effect of PT in both in vivo tumor models. Therefore, the PT+MTX combination may present a promising therapeutic approach for different types of cancer.